Efektivitas Supervisi Akademik dalam Meningkatkan Kemampuan Guru Menggunakan Metode Contextual Teaching And Learning - Machsun, Toha (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study aims to analyze the effectiveness of academic supervision in improving teacher performance using the Contextual Teaching and Learning (CTL) method in the learning process at MTs. Muhammadiyah 1 Gresik. This research was conducted in the even semester of even semester of the 2018-2019 academic year. The research subjects were several teachers of MTs Muhammadiyah 1 Gresik who were identified as having difficulties in using the CTL method. Data collected through teacher performance tests before and after clinical supervision. supervision. Furthermore, the data was analyzed with a quantitative approach. quantitative approach. The research findings show that the implementation of academic supervision with a clinical approach is quite effective. This is marked by the average value of teacher performance in managing learning program using the CTL method after academic supervision with academic supervision with a clinical approach amounted to 77.1%. This means that the result has exceeded the minimum limit of class learning completeness, namely 75%. There are 28 teachers out of 30 teachers (93.3%) who have been thoroughly declared complete in using the CTL learning method with the average score reached 75% / more